Strengthening Religious Moderation through Digital Publication of Islamic Education Journal - Rasyidin, Rasyidin; Fahruddin, Ahmad Hanif (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2024)
This study employs a library research method to examine the role of the Tadris Journal in promoting religious moderation in Islamic education at IAIN Madura. Using literature as the primary data source, it provides an in-depth analysis of religious moderation through academic publications. Data was collected using manual coding based on discourse analysis principles and analyzed with NVivo software for rigor and transparency. The research focuses on three volumes of the Tadris Journal (Vol. 14 No. 2, 2019; Vol. 18 No. 1, 2023; Vol. 18 No. 2, 2023), selected for their relevance to religious moderation. These publications align with the Ministry of Religious Affairs' initiatives to strengthen religious moderation during 2019–2023. Critical Discourse Analysis (CDA) by Norman Fairclough was applied to analyze the interaction between text, context, and power structures, encompassing thematic identification, discourse evaluation, and socio-political contextualization. The findings reveal the Tadris Journal's key role in addressing socio-religious issues in Madura, a region marked by radicalism and religious violence. Themes include countering radical conservatism, fostering peace, promoting ethical values, enhancing intra-faith relations, and embracing digital transformation. These efforts showcase a strategic approach to embedding religious moderation in higher education. The study underscores the importance of digital platforms in amplifying discourse on religious moderation and calls for innovative digital tools to expand religious literacy. Collaboration between academic institutions and policymakers is recommended to foster tolerance and peaceful coexistence across diverse socio-religious settings.